Water‐Enhanced Multicolor Electrochromism in Nickel‐Catecholate MOFs - Qi Zhao; Jing Yang; Xingyang Wang; Wanwan Wang; Yulin Gao; Xue Chen; Jianguo Sun; Hao Yuan; Yu Liu; Jinwoo Park; Lewis Kien Juen Ting; Qing Wang; et al. (Advanced Science, 2025)
Abstract Metal–organic frameworks (MOFs) represent a novel electrochromic material system but are limited in tunable color versatility, rapid switching speed, and long‐term cycling stability. A new multicolor electrochromic behavior is reported, with transitions from green to blue to purple, in conducting nickel‐catecholate (Ni‐CAT‐1) MOFs. The system significantly improves cycling stability to 2000 cycles and reduces switching time to 3.6 s, both of which outperform most state‐of‐the‐art MOF systems. An in‐depth understanding of the coloring mechanism, particularly the interconversion among C─O, C─O•, and C = O groups is revealed. Water molecules play diverse roles in this redox process. Specifically, water molecules induce distortions in Ni─O bonds, facilitating C = O bond formation and expediting the oxidized coloring process, while also aiding the dissociation of ions from solvation complexes to enhance the reduction process. The practical applications of these findings are demonstrated by designing flexible multicolor electrochromic devices (FMEDs) for use in camouflage, flexible displays, and augmented reality (AR).